A Hypothesis of Architectural Environment Exercise for Actor Training (Continuous exercise space workshop – A model): هيثم عبد الرزاق علي (Al-Academy, 2019)
The peculiarity of the theater does not lie in its dramatic content because many literary genres and other artistic styles share with it in this content. The peculiarity of the theater lies in contemplating the drama through what is architectural, and this architectural axis is what distinguishes its character. It is a spatial poetry which is composed by the laws of physics and chemistry, (Weight, height, distance, rhythm, gravity, impulses and chemical excretions). i.e., what cannot be expressed in words. This is a game of space to exchange and organize energy and communicate in space by the living body, which contains the possibilities of the living drawing in space: in the time and place. This research deals with the importance of the hypothesis of the exercise as an architectural environment to stimulate and develop the skill of the living body to write and compose the space at the time and place in the framework of the primacy of the image culture on the text culture.